John H. Herry, Digest of the Laws and Ordinances of the City of Little Rock, with the Constitution of the State of Arkansas; General Incorporation Laws; and All Acts of the General Assembly Relating to the City 149 (1882) - (:unkn) unknown (My University, 1881)
Required a payment and license for the operation of a shooting gallery or pistol gallery. Payment set at twenty-five dollars per year.
Keywords: SHOOTING RANGES OR GALLERIES